A 2-free-end flexor carpi radialis tendon graft for treating a complex index finger extensor tendon injury - Colasanti, Giovanni Battista; Pari, Carlotta; Puzzo, Agnese; Paderni, Stefania; Goretti, Claudio; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background: Volar plating has increasingly become the most used technique for the treatmentof unstable distal radius fractures due to the low soft-tissue disturbance and its biomechanical reliability,which allows the early mobilization of the wrist. One of the main goals of the volar locking compressionplates design is to avoid those soft tissue complications historically associated to the dorsal plating. However,extensor tendon complications can not be completely excluded. Method: The authors report the case of apatient with a complete rupture of the index finger extensor tendons after volar plate fixation of the distalradius. Due to the presence of a severe tendons retraction with a 4-centimeter gap and the neighbouringsoft tissues damage, it was decided to fill the gap with a 2-free-end autograft harvested from the FlexorCarpi Radialis (FCR) tendon, using the volar surgical approach performed to remove the plate. Results:At the 2-month follow-up, the patient showed the complete recovery of the flexion-extension movements.Conclusions: Even though the 2-free-end FCR tendon graft is not commonly reported for the reconstructionof extensor tendons defects, we assume it deserves to be considered as an adequate technique whenever theneighbouring tendons are critically compromised.